Dispatches from the Arab Spring Understanding the New Middle East. - Amar, Paul (University of Minnesota Press, 2013)
Bringing together contributors uniquely attuned to the pulse of the region, Dispatches from the Arab Spring offers an urgent analysis of a remarkable ongoing world-historical event that is widely misinterpreted in the West. An unparalleled introduction to the changing Middle East, it offers the most comprehensive and accurate account of the uprisings that profoundly reshaped North Africa and the Middle East.